Rehabilitasi Medik Dengan Metode William Flexion Exercise Pada Pasien Low Back Pain Pasca Trauma: Medical Rehabilitation Outcomes Using the William Flexion Exercise Method in Post-Traumatic Low Back Pain Patients - Yustisia, Meuthia Sendy; Safei, Imran; Putra, Fadil Mula; Muchsin, Achmad Harun; Pangnguriseng, Utomo A. (Jurnal Abdi Keperawatan dan Kedokteran, 2026)
Post-traumatic Low Back Pain (LBP) is one of the most common musculoskeletal disorders and can lead to prolonged pain and limitations in daily activities. Medical rehabilitation using the William Flexion Exercise (WFE) method is a therapeutic approach that aims to reduce pain and improve lumbar function through structured flexion movements. This study aimed to describe the outcomes of medical rehabilitation using the William Flexion Exercise method in patients with post-traumatic low back pain at Ibnu Sina Hospital, Makassar. This study employed a quantitative descriptive design with a cross-sectional approach. A total of 60 patients were selected using purposive sampling based on inclusion and exclusion criteria. Respondent characteristics included age, sex, and diagnosis. The research variables consisted of pain intensity as the dependent variable and the William Flexion Exercise intervention as the independent variable. The instruments used were the Visual Analog Scale (VAS) to assess pain intensity (pain at rest, pain during movement, and tenderness) and the Roland-Morris Disability Questionnaire (RMDQ) to measure functional disability. Data were analyzed descriptively using frequency distributions and percentages. The results showed that the majority of respondents were female (65%) and belonged to the adult age group (53.3%), with the most common diagnosis being non-specific LBP (70%). After undergoing rehabilitation with the WFE method, pain intensity improved significantly, with most patients categorized as having mild pain: at rest (63.3%), during movement (65%), and on tenderness (80%). Additionally, 35% of patients no longer experienced pain at rest. Functional disability outcomes were also favorable, with 70% of respondents categorized as having mild disability and no patients experiencing severe disability. In conclusion, medical rehabilitation using the William Flexion Exercise method demonstrates favorable outcomes in reducing pain intensity and improving functional ability in patients with post-traumatic low back pain.